Research of the Dynamic Characteristic of the Front End Accessory Drive System of Automobile Engine Considering OAP - Wang Erhua; Wu Bo; Hu Youmin; Yang Shuzi (Jixie chuandong)
The dynamic characteristics of the front end accessory drive（ FEAD） system of automobile engine can affect the noise,vibration and harshness,and the safety,comfort of automobile directly. A mathematical model of nonlinear rotational vibration of FEAD system with an overrunning alternator pulley（ OAP） is established. The influence of OAP on FEAD system is analyzed,and the influence of OAP stiffness on the angle fluctuation of tension pulley and B1 and B3 is gotten. The research can provide some essential theoretical basis and practice guidance for the optimization of FEAD system and OAP.